EKSISTENSI PEREMPUAN DALAM ANIME ARTE - Ni Putu Figlia Ayu Salsa Dimita; Wayan Nurita; Ni Luh Gede Meilantari (Jurnal Daruma : Linguistik, Sastra dan Budaya Jepang, 2022)
The analysis in this study aims to examine and describe the existence of the main female character in the anime Arte. This research is descriptive-qualitative type. The data source used in this study is an anime entitled Arte. The data obtained were analyzed using existentialist feminism theory. The method and technique of data collection in this research is the listening method with the advanced note-taking technique, namely by listening repeatedly to the Arte anime, then recording dialogues that show their existence as women.The methods and techniques of data analysis in this study used a qualitative descriptive method which was described using an informal method, namely describing it in Indonesian words that are easy to understand. The results of the study found that the main female character in the anime Arte based on Simone De Beauvoir's existentialist feminism theory can achieve transcendence based on four strategies, namely, 1. Women can work, 2. Women can become intellectuals, 3. Women achieve socialist transformation of society. , 4. Women can refuse their otherness.